(untitled) (Latakia University Journal -Basic Sciences Series, 2022)
This research deals with the quality of groundwater in some wells in Lattakia Governorate, by collecting 20 water samples distributed over most of the formations in the research area during the year 2015, and conducting some chemical analyzes for them, and then treating those results in order to assess the quality of groundwater, and to know their suitability for drinking water and irrigation according to the Syrian Standard Specifications and some internationally approved standards. The research concluded that the water in the area is mainly of bicarbonate-calcareous-magnesian type. Most of the water collected from the samples in harsh, and some of it is very harsh. In addition, all the collected samples are chemically fresh water that is suitable for drinking according to the Syrian Standard Specification (2007). Where the values of the concentrations of cations and anions dissolved in it are within the permissible limits, and they are suitable for irrigation purposes and for all agricultural crops according to the approved international standards.